2023
DOI: 10.3390/ijms24032410
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Modulation Results in Aberrant Isoforms and Protein Products of p53 Pathway Genes and the Sensitization of B Cells to Non-Genotoxic MDM2 Inhibition

Abstract: Several molecular subtypes of cancer are highly dependent on splicing for cell survival. There is a general interest in the therapeutic targeting of splicing by small molecules. E7107, a first-in-class spliceosome inhibitor, showed strong growth inhibitory activities against a large variety of human cancer xenografts. Chronic lymphocytic leukaemia (CLL) is a clinically heterogeneous hematologic malignancy, with approximately 90% of cases being TP53 wild-type at diagnosis. An increasing number of studies are ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Interestingly, we observed an alternatively spliced form of p21 (Figure S18). This larger p21 isoform was recently reported by the Lunec group, which demonstrated that when cells were treated with E7107 (pladienolide analogue), p21 L retained an intron and lost its nuclear localization signal, resulting in a loss of CDK inhibitory activity . In addition, they observed alternative splicing of p53 with the pladienolide analogue E7107, which we did not observe with the meayamycins.…”
Section: Resultssupporting
confidence: 78%
“…Interestingly, we observed an alternatively spliced form of p21 (Figure S18). This larger p21 isoform was recently reported by the Lunec group, which demonstrated that when cells were treated with E7107 (pladienolide analogue), p21 L retained an intron and lost its nuclear localization signal, resulting in a loss of CDK inhibitory activity . In addition, they observed alternative splicing of p53 with the pladienolide analogue E7107, which we did not observe with the meayamycins.…”
Section: Resultssupporting
confidence: 78%
“…The loss of p21 reduces the protective effect of MDM2 inhibitors on DNA and boosts the effectiveness of MDM2 and DNAdamaging agents when combined. Furthermore, in a previous study by our group, we showed that p21 is vulnerable to inhibition with a spliceosome inhibitor E7107, and a novel p21 abberant isoform with a compromised cyclin-dependent kinase inhibitory activity is generated [22]. The protective effect of normal p21-mediated growth inhibition is lost with the switch to the aberrant p21 isoform that is unable to localize to the nucleus, thus sensitising E7107 treated cells to the MDM2 inhibitor RG7388.…”
Section: Discussionmentioning
confidence: 84%
“…The details of Sanger sequencing of SF3B1 in primary CLL samples have been described in a previous study [22]. The TP53 mutational status of CLL samples was assessed by next-generation sequencing (using Roche 454 GS FLX and Illumina MiSeq platforms) in all samples.…”
Section: Patient Sample Informationmentioning
confidence: 99%
“…MDM2, the strongest p53-negative regulator discovered so far, can bind to the p53 protein and exert corresponding biological regulation [71]. Many studies show that MDM2 promotes the self-renewal and differentiation of mouse and human airway epithelial basal stem cells by regulating p53 protein and induces cell cycle arrest and apoptosis [72], which implies that MDM2 may regulate the differentiation and self-renewal of SSCs through the activated p53 pathway.…”
Section: Discussionmentioning
confidence: 99%